ANALISIS EFISIENSI BIAYA PERSEDIAAN MENGGUNAKAN METODE EOQ (ECONOMIC ORDER QUANTITY) PADA PT. XYZ - Dea Misbachul Umami; Mohammad Fuad Fauzul Mu'tamar; Rakhmawati Rakhmawati (JURNAL AGROTEKNOLOGI, 2018)
Inventory control is one of the important things of working capital in a company. Economic Order Quantity (EOQ) could be decided from the safety stock, maximum inventory, and reorder point in a company. The aim of the research was to know the number of stock and inventory cost savings. The research used EOQ method on controlling the packaging cup 240 ml and carton box to know the amount of safety stock, maximum inventory, and reorder point in PT. XYZ. The result showed that the sum of buying the material based on EOQ method in the 2015, 2016 and 2017.In the 2015 the amount f packaging cup 240ml were 1.492.031 cups, the amount f carton box were 25.164 cartons, in the 2016 the sum of packaging cup 240 ml were 1.492.084 cups, the sum of cartoon box were 24.697 cartons, while in the 2017 the sum of packaging cup were 240 cups. Using the EOQ method can be known that inventory cost savings as the result of the decreasing of the order. Safety stock were around 447.406 for a 240ml cups and 9.319 for cartons box. Maximum inventory based on EOQ method were around 992.445 for 240 ml cups and 20.549 for cartons. Reorder point based on EOQ method were around 860.066 for a 240ml cups and 17.918 for cartons. Keywords: EOQ, inventory control, maximum inventory, reorder point, safety stock